MicroRNAome: Potential and Veritable Immunomolecular Therapeutic and Diagnostic Baseline for Lingering Bovine Endometritis - Oladejo, Ayodele Olaolu; Li, Yajuan; Wu, Xiaohu; Imam, Bereket Habte; Shen, Wenxiang; Ding, Xue Zhi; Wang, Shengyi; Yan, Zuoting (Frontiers in Veterinary Science, 2020)
The bovine endometrium is a natural pathogen invasion barrier of the uterine tissues' endometrial epithelial cells that can resist foreign pathogen invasion by controlling the inflammatory immune response. Some pathogens suppress the innate immune system of the endometrium, leading to prolonged systemic inflammatory response through the blood circulation or cellular degradation resulting in bovine endometritis by bacterial endotoxins. The microRNA (miRNA) typically involves gene expression in multicellular organisms in post-transcription regulation by affecting both the stability and the translation of messenger RNA. Accumulated evidence suggests that miRNAs are important regulators of genes in several cellular processes. They are a class of endogenous non-coding RNAs, which play pivotal roles in the inflammatory response of reproductive diseases. Studies confirmed that miRNAs play a key regulatory role in various inflammatory diseases by mediating the molecular mechanism of inflammatory cytokines via signal pathways. It implicates some miRNAs in the occurrence of bovine endometritis, resorting to regulating the activities of some inflammatory cytokines, chemokine, differentially expressed genes, and protein through modulating of specific cellular signal pathways functions. This review dwells on improving the knowledge of the role of miRNAs involvement in inflammatory response as to early diagnosis, control, and prevention of bovine endometritis and consequently enlighten on the molecular improvement of the genes coded by various differentially expressed miRNA through the need to adopt recent genetic technologies and the development of new pharmaceutical preparations.